The Effect of Advertising, Quality Perception, and Brand Image on Consumer Purchase Decisions at Next Store Distro Rantauprapat - Rambe, Putra Azhari; Safri, Hayanuddin; Anggraen, Elisa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research aims to analyze the influence of advertising, perceived quality, and brand image on consumer purchasing decisions at Next Store Distro Rantauprapat. The background of the study is based on the increasing competition in the distro business, which requires companies to optimize marketing strategies in order to attract attention and build consumer loyalty. This study employs a quantitative approach with a survey method. Data were collected through questionnaires distributed to consumers of Next Store Distro Rantauprapat, with a specific sample size determined using a purposive sampling technique. Data analysis was conducted using validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results indicate that advertising has a positive and significant influence on consumer purchasing decisions. Perceived quality also has a significant effect, meaning that the higher the quality perceived by consumers, the greater their tendency to make a purchase. In addition, brand image significantly influences consumer trust and loyalty. Simultaneously, advertising, perceived quality, and brand image have a significant impact on consumer purchasing decisions at Next Store Distro Rantauprapat. The findings emphasize the importance of integrated marketing strategies in enhancing purchasing decisions through attractive advertising, consistent product quality, and a strong brand image.